Effect of supplementing lactic acid bacteria on the performance of female cattle calves fed grain based or grainless concentrate mixture - DAS, K C; KAMRA, D N; PATHAK, N N (The Indian Journal of Animal Sciences, 2014)
Crossbred (Bos indicus x Bos taurus) female cattle calves (32) at the age of 5 months were divided into 4 groups of 8 animals each and were fed gram based concentrate with lactic acid bacteria (GC), grain based concentrate without lactic acid bacteria (GCo), grainless concentrate with lactic acid bacteria (GoC) and grainless concentrate without lactic acid bacteria (GoCo). The. milk was fermented with lactic acid bacteria i.e. Lactobacillus acidophilus. L.jugarti and L.casei separately and was mixed with the concentrate mixture at the time of feeding. About 50% of the dry matter requirement of the animals was met With concentrate mixture and green fodder was fed ad lib. It is concluded that grain can be replaced With wheat bran in the concentrate mixture of crossbred heifers without adversely affecting the performance of animals and that there was no advantage of feeding lactic acid bacteria in both grain based and grainless diets of female crossbred cattle calves when the rumen was fully developed.